Maldánidos (Polychaeta) del Caribe Mexicano con una clave para las éspecies del Gran Caribe - Jiménez-Cueto, M Soledad (Universidad de Costa Rica, 1997)
On the basis of 92 speciQlens collected in Mexican Caribbean coasts, seven species in three subfamilies were identified.- Notoproctinae: Notoproctus oculatus? Arwidsson, 1907; Nicomachinae : Micromaldane ornithochaeta Mesnil, 1879, Nicomache antillensis Augener, 1922 and Petaloproctus socialis Andrews, 1 89 1 ; Euclymeninae: Axiothella mucosa (Andrews, 1 89 1 ), Euclymene coronata Verrill, 1 900, and Isocirrus corallicolus (Treadwell, 1929) combo nov. Three other species are included because of their type or reference materials were examined, the maldaninae Sabaco elongatus (Verrill, 1 873) and Maldane sarsi Malmgren, 1865, from the Central Atlantic and recorded in the Grand Caribbean region; Maldane atlantica McIntosh, 1 885, is regarded as indete,rminable.lti a commentary on the species ofAxiothella Verrill, the genus is redefined, species are grouped accordin to their anal cilti and number of uncini in first setigers. Further, the status of A. rubrocincta complexa Berkeíey &"'Berkeley is risento species level; it is suggested that A. crozetensis Gillet and Microclymene tricirrata ArWidssoli should be placed in Clymenura Verrill, A. quadrimaculata Augener should be included in Microclymene Arwidsson, the placement of A. cataliniaHaitman in Maldanella McIntosh is confirmed and because of the definition of this genus, A byssoclymene Hartman, with A. annularis Haitman as its type and only species, shoul¡l be regarded as a junior synonym of Maldanella. A key!O' identifY all the recorded species of maldanids in the Grand Caribbeall region is also included.